Learning from the Mediators: How Student Affairs Staff at Christian Colleges Combine Care and Conviction in Their Responses to LGBTQ+ Students. Issue 4 (8th August 2022) - Glanzer, Perry L.; Graber, Britney N.; Cockle, Theodore F.
Abstract: The relationship between faith-based institutions and students who identify as LGBTQ+ has attracted considerable attention of late. Most of this scholarly attention, however, has focused upon the students themselves. In this article, we examine the contemporary experience of 371 student affairs leaders (SALs) who serve as the primary mediators between the desires and demands of LGBTQ+ advocates, scholars, and students, and the policies of current administrators. This article reports on previously unexplored data from a larger grounded theory study on Christ-enlivened student affairs to answer the research question: How do SALs at Christian universities approach LGBTQ+ students in light of the Christian mission of their institutions? Data were collected using a qualitative questionnaire of 301 SALs, as well as extended interviews with 70 SALs. Participants' moral/theological responses included a collection of Christian virtues and rules. They indicated a range of helpful practices—including how they handled campus groups—but generally agreed on the dearth of training and education they had received on the topic. In our discussion, we compare our findings to the recommendations of previous scholars before elaborating our own list of recommendations. Our suggestions for Christian campuses include a re-imagined policy statement, a commitment to education rather than training, a focus on the spiritual needs of students, and some recommendations for LGBTQ+ campus groups.